Comparative Effectiveness of Needle Aspiration Vs Incision and Drainage in Management of Peritonsillar Abscess - Abdul Manan Khan, Aria Masoom (Pakistan Journal of Medical & Health Sciences, 2023)
Background: An accumulation of pus between the tonsil’s fibrous capsule and the pharynx’s superior constrictor muscle is known as a peritonsillar abscess. Objective: To assess the Comparative effectiveness of Needle aspiration VS incision and drainage in management of peritonsillar abscess Methodology: This randomized control trails was conducted at the Department of ENT, Bolan Medical College / Complex Hospital, Quetta from January 2023 to June 2023 after taking approval from the research committee of the institute. In the current study, totally 80 patients were enrolled and they were divided into Group A and Group B. Forty patients were enrolled in each group. 40 patients in group A received treatment by needle aspiration while Group B patients received treatment by incision and drainage. Data analysis was done using SPSS version 23. The data was described using descriptive statistics. The chi-square test was employed for qualitative variables and the independent sample’s t-test for quantitative variables. A p-value of less than 0.05 was deemed significant. Results: In the current study, totally 80 patients were enrolled and they were divided into Group A and Group B. Forty patients were enrolled in each group. The male patients in group A were 25 (62.5%) and female patients were 15 (37.5%). In group B, male patients were 23 (57.5%) and female were 17 (42.5%). On the basis of age and gender, patients in both the groups were almost similar (p=less than 0.05). In case of group A, 30 (75%) patients were successfully managed while in group B, 33 (82.5%) patients were treated successfully. In patients of group A, repeat drainage on day first was required in 8 (20%) while in group B it was required in 7 (17.5%) patients. In patients of group A, third procedure on day 2 was required in 2 (5%) patients while it was not required for any patients of group B on day second. Conclusion: Our research showed that needle aspiration is a less invasive and similarly effective procedure in comparison to incision and drainage in the therapy of peritonsillar abscess. Keywords: Effectiveness; Needle aspiration; Incision; Drainage; Peritonsillar abscess